The Impact of Tebas on the Economy of Ngawi Farmers Reviewed from the Ethics of Sharia Business - Yusron Hanafi; Agus Sriyanto; Tri Wahyu Widodo (Universitas KH. Abdul Chalim Mojokerto, 2025)
The total area of Ngawi Regency is 1,298.58 km2, of which 506.6 km2, or about 40% is made up of rice fields. According to the data, farmers employ the bulk of Ngawi's people. Mango fruit is the second most abundant good after rice, as most Ngawi people grow mango trees in front or behind their homes. When harvest season rolls around, farmers have trouble finding buyers who will purchase their crops in an honest and profitable manner. This is because buyers, also known as penebas, use the Tebas system to complete the purchase process for these two commodities, which means that the system cannot fulfill the wishes of both parties involved in the transaction if It also goes by the name